Wildfire Surveillance System for Peat Soil Area - BUNIA, SHAH; Borhan, Azuwein; Ishak, Maizul (Progress in Engineering Application and Technology, 2023)
The purpose of this project is to develop a Wildfire surveillance system for peat soil areas using IoT and smart systems. The system will use microcontrollers and sensors to collect and evaluate data such as temperature and smoke presence, and a GSM module will be used to transmit this data to the user. The Blynk app will serve as the main interface for the user to access this information and take action to respond to the wildfire. The goal is to commercialize the prototype and use it as a tool for wildfire prevention and conservation.